Estado actual de las herramientas de manejo del paisaje en Filandia, Quindío, Colombia - Osorio Giraldo, Angélica María (2022)
In the foothills of the Colombian central mountain range, bordering between the municipalities of Filandia (Quindío) and Pereira (Risaralda), It is located the middle basin of the Canyon of Barbas River, consisting of two large wooded areas, the Bremen-La Popa Forest Reserve and the Barbas river canyon, which, despite being surrounded by an agricultural matrix, have a high number of endemic and threatened fauna and flora species. In 2005, seeking to improve the connectivity of this landscape, the Municipal Office of Filandia, in agreement with the Alexander von Humboldt Institute, implemented a series of practices called Landscape Management Tools. From the moment of their realization, most of the researches made, has focused only on evaluating the contribution of biological corridors to connectivity, leaving aside the evaluation of the other tools, and without considering all the elements composing the landscape. During the first four-month period of 2017, a qualitative observation protocol was applied to determine the current state of four tools (biological corridors, mini-corridors, live fences and trees scattered in pasture, and through semi-structured interviews the perceptions of producers, owners and decision makers were collected about what these tools have represented in environmental and economic terms for their farms. It was found that live fences and trees scattered in pasture have disappeared, respectively, by 57% and 68%, while all of the biological corridors and mini- corridors implemented still remain. All the producers consulted highlighted the environmental benefits offered by the tools over the economic benefits. The totality of the decision makers interviewed, focused on the need to continue with a second phase of the project, through the implementation of wildlife passes, although they state that today they do not have the financial resources to execute them.